Business Information Systems : 20th International Conference, BIS 2017, Poznan, Poland, June 28–30, 2017, proceedings /: 20th International Conference, BIS 2017, Poznan, Poland, June 28–30, 2017, proceedings. ([2017]) - Unknown
No abstract available